6-Thioguanine Nucleotide Levels Are Associated With Mucosal Healing in Patients With Crohn's Disease. Issue 12 (17th May 2018) - Mao, Ren; Guo, Jing; Luber, Raphael; Chen, Bai-Li; He, Yao; Zeng, Zhi-Rong; Ben-Horin, Shomron; Sparrow, Miles P; Roblin, Xavier; Chen, Min-Hu
Abstract: Background: Level of 6-thioguanine nucleotides (6-TGN) has been reported to be associated with clinical remission in patients with Crohn's disease (CD) receiving maintenance treatment with thiopurines. Whether 6-TGN levels are associated with mucosal healing (MH) has seldom been investigated. We aimed to assess the correlation between 6-TGN levels and MH in patients with CD. Methods: This was a retrospective, cross-sectional, observational, multicenter study of 119 patients with CD treated with thiopurines in 3 inflammatory bowel disease referral centers (France, Australia, and China) between June 2012 and April 2016. Established CD patients who underwent ileocolonoscopy during thiopurine treatment were included. MH was defined as simple endoscopic score–CD <3. Univariate and multivariable regression analyses were used to evaluate variables associated with MH. Results: The mean concentration of 6-TGN in the MH group was higher compared with that in the non-MH group (359.0 ± 226.7 pmol/8 × 10 8 red blood cell count [RBC] vs 277.1 ± 170.5 pmol/8 × 10 8 RBC; P = 0.017). The cutoff 6-TGN concentration of 397.3 pmol/8 × 10 8 RBC was 86.7% specific to MH, with a sensitivity of 35.3% and area under curve (AUC) of 0.631 ( P = 0.010). On multivariable analysis, 6-TGN levels were associated with MH (odds ratio [OR], 3.287; 95% confidence interval [CI], 1.348–8.017; P = 0.009) whereas late initiation of AZA (longer duration from disease onset) was inversely associated with MH (OR, 0.972; 95% CI, 0.954–0.991; P = 0.004). Conclusions: Higher 6-TGN levels are independently associated with a reduced rate of endoscopically active disease and a higher rate of mucosal healing in CD patients. Prospective studies of adequate sample size are required to confirm these findings.